A Review of Unemployment, Employment, Participation, and Wage Rates for Aboriginals and Non-Aboriginals — 2007-2019 - Oppenheimer, Robert J. (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2020)
For Aboriginals in Canada, their employment and participation rates decreased, and their unemployment rate remained the same in 2019. In contrast, non-Aboriginals' unemployment, employment, and participation rates improved. These rates and wage rates are and have historically been more favourable for non-Aboriginals than for Aboriginals. These rates are examined by gender, age, and sector, as well as for Métis and First Nations.